RATIB SAMAN: ACTIVITIES DURING THE GRAVE PILGRIMAGE AS LOCAL WISDOM OF THE TANJUNG PAUH MUDIK COMMUNITY - Ramadani, Yolla; _, Hafizah (Jurnal Ilmu Pendidikan Ahlussunnah, 2024)
This article examines the activities of Ratib Saman during grave pilgrimages in the Tanjung Pauh Mudik community, Kerinci Regency as well as the pilgrim's motives in the Grave Pilgrimage Tradition in Talang Berdoa (Cemetery Land). The tradition of visiting graves is a tradition that has existed for a long time, there are even indications that this tradition existed before the arrival of Islam. Even though eras and times have changed, the tradition of grave pilgrimage has not been eroded by the times, the interest and intention of pilgrims to visit existing graves continues and is even getting busier. The method used in this research is field research with a qualitative-descriptive approach, data collection tools are participant observation, interviews and document study. The results of the research show that people's motivation for carrying out ratib saman during grave pilgrimages is because it has the meaning and symbol of praying for the spirits of family members who have died. Apart from that, ratib saman is also a custom passed down from generations to generations which must be preserved as local wisdom of the people of Tanjung Pauh Mudik, Kerinci Regency.